Drivers and deterrents of entrepreneurial enterprise in the risk‐prone Global South. Issue 1 (January 2017) - Lundy, Brandon D.; Patterson, Mark; O'Neill, Alex
Abstract: Through the case of Guinea‐Bissau, this article considers how small‐scale, often cross‐border entrepreneurs mitigate risk and establish resilient businesses able to cope with ongoing political and economic shocks. Nineteen interviews and 153 surveys were conducted over two months with business leaders and regulators within the commercial centers and markets of Guinea‐Bissau to assess entrepreneurial profiles and activities. Findings show that small‐scale private investment from the Global South is increasing. Through thematic analysis, 18 different drivers of foreign business and 23 impediments to foreign entrepreneurship and investment were identified within this risk‐prone environment. Limited assets imply limited opportunities, suggesting a need to mobilize all available resources to achieve entrepreneurial success. The implications of this research are that resiliency for these foreign investors has improved and risks are mitigated through established social capital that can be converted into financial capital, linked social–business networks across borders, microenvironmental knowledge, and maintaining relatively small businesses able to fly "under the radar." In understanding foreign entrepreneurs' motives, the social and structural undergirding of South–South investment is exposed.